Revisiting ancient DNA insights into the human history of the Pacific Islands. Issue 1 (19th March 2019) - SPRIGGS, MATTHEW; VALENTIN, FREDERIQUE; BEDFORD, STUART; PINHASI, RON; SKOGLUND, PONTUS; REICH, DAVID; LIPSON, MARK
ABSTRACT: We respond to issues raised in the recent Forum on "Ancient DNA and its contribution to understanding the human history of the Pacific Islands" in A rchaeology in O ceania by Bedford et al . We first present an emerging model for the early peopling of Vanuatu combining the genetic and archaeological evidence. Second, we respond specifically to the criticisms of two contributors: Matisoo‐Smith and Sand. We discuss various misconceptions about the Teouma Lapita cemetery and about sampling issues in DNA research.